Conjugated Addition of Amines to Electron Deficient Alkenes: A Green Approach - Anindita Mukherjee; Rana Chatterjee; Aramita De; Satyajit Samanta; Sachinta Mahato; Nirnita Chakraborty Ghosal; G. V. Zyryanov; Adinath Majee (Chimica Techno Acta)
A very simple approach has been developed for conjugate addition of a variety of aliphatic and aromatic amines to electron deficient alkenes in presence tea extract at room temperature. General applicability, operational simplicity, aqueous media, mild reaction conditions, environment friendly, high yields and applications of inexpensive and easily available catalyst are the advantages of the present procedure.